Excellent Compatibility of Solvate Ionic Liquids with Sulfide Solid Electrolytes: Toward Favorable Ionic Contacts in Bulk‐Type All‐Solid‐State Lithium‐Ion Batteries. Issue 22 (3rd August 2015) - Oh, Dae Yang; Nam, Young Jin; Park, Kern Ho; Jung, Sung Hoo; Cho, Sung‐Ju; Kim, Yun Kyeong; Lee, Young‐Gi; Lee, Sang‐Young; Jung, Yoon Seok
Abstract : The excellent stability of sulfide solid electrolytes with solvate ionic liquids Li(triethylene glycol dimethyl ether)bis(trifluoromethanesulfonyl)imide (Li(G3)TFSI), and their application for high‐performance, all‐solid‐state lithium‐ion batteries are successfully demonstrated. The addition of a small amount of Li(G3)TFSI gives an alternative ionic pathway through normally poor solid–solid contacts, leading to a dramatic increase in LiFePO4 composite electrode capacity.